Performance of rapid tests and algorithms for HIV screening in Abidjan, Ivory Coast. - Loukou, Y G; Cabran, M A; Yessé, Zinzendorf Nanga; Adouko, B M O; Lathro, S J; Agbessi-Kouassi, K B T (Journal of the International Association of Providers of AIDS Care, 2014)
Seven rapid diagnosis tests (RDTs) of HIV were evaluated by a panel group who collected serum samples from patients in Abidjan (HIV-1 = 203, HIV-2 = 25, HIV-dual = 25, HIV = 305). Kit performances were recorded after the reference techniques (enzyme-linked immunosorbent assay). The following RDTs showed a sensitivity of 100% and a specificity higher than 99%: Determine, Oraquick, SD Bioline, BCP, and Stat-Pak. These kits were used to establish infection screening strategies. The combination with 2 or 3 of these tests in series or parallel algorithms showed that series combinations with 2 tests (Oraquick and Bioline) and 3 tests (Determine, BCP, and Stat-Pak) gave the best performances (sensitivity, specificity, positive predictive value, and negative predictive value of 100%). However, the combination with 2 tests appeared to be more onerous than the combination with 3 tests. The combination with Determine, BCP, and Stat-Pak tests serving as a tiebreaker could be an alternative to the HIV/AIDS serological screening in Abidjan.